2020
DOI: 10.1007/s11306-020-01712-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct serum metabolomic signatures of multiparous and primiparous dairy cows switched from a moderate to high-grain diet during early lactation

Abstract: Introduction Feeding of high-grain diets is common in cows during early lactation, but increases the odds of metabolic derailments, which can likely be detected as undesirable shifts in the serum metabolome signature. Objectives The present study aimed to identify the metabolic signatures of the serum metabolome of early lactation dairy cows switched from a moderate to a high-grain diet. Methods Targeted ESI-LC-MS/MS-based metabolomics was used to characterize metabolic alterations in the serum of early la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The difference in plasma BAs and ACs concentrations of weaning groups was probably due to their different dietary composition as the carbohydrates rich diet may result in higher levels of BAs [ 52 ]. A high concentration of serum taurine was observed in high-grain fed dairy cows [ 53 ]. A decreased level of plasma acylcarnitines was observed after feeding calves with a limited amount of MR in another study [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in plasma BAs and ACs concentrations of weaning groups was probably due to their different dietary composition as the carbohydrates rich diet may result in higher levels of BAs [ 52 ]. A high concentration of serum taurine was observed in high-grain fed dairy cows [ 53 ]. A decreased level of plasma acylcarnitines was observed after feeding calves with a limited amount of MR in another study [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taurine can be derived directly from the diet, absorbed through the epithelial cells and transported to the blood [ 17 ]. A significant increase in serum taurine concentration was reported with high-grain feeding in dairy cows [ 53 ]. However, endogenous synthesis of taurine from methionine and cysteine majorly takes place in liver and tissues [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decline and shortage of pasture quality, together with increased exercise and physical activity of grazing Jersey cattle, have resulted in Jersey cattle relying mainly on supplemented concentrates to meet their energy needs, which have a high fat content, leading to increased fat metabolism [71]. A similar result was found in cows, with an increase in fat catabolism in high-concentrate-fed cows [72]. The results also showed that concentrate supplementation signi cantly affected serum metabolites and promoted lipid synthesis in yaks [24].…”
Section: Serum Metabolitesmentioning
confidence: 90%
“…Details concerning the determination of the serum metabolome and the results related to feeding and parity are given in Pacífico et al (4). Briefly, 10 µl of aliquots of serum samples were processed using a targeted metabolomics approach based on the Biocrates MxP R Quant 500 kit (Biocrates Life Sciences AG, Innsbruck, Austria).…”
Section: Serum Metabolomementioning
confidence: 99%
“…The risk of health disorders deriving from impaired liver function is especially high during early lactation (2), and the disorders induced by high-grain diets further compromise liver function by enhancing the release and translocation of microbial endotoxins into the systemic circulation (1) as well as impairing the hepatic lipid and bile acid metabolism (3). In fact, recent research showed major metabolic shifts in bile acid metabolism in response to high-starch diets (4), and this finding was consistent with increased liver enzyme concentrations, e.g., aspartate aminotransferase (AST), glutamate dehydrogenase (GLDH), γ-glutamyl-transferase (GGT), and alkaline phosphatase (AP) during early lactation (5). These effects were particularly pronounced in primiparous cows, thus highlighting the already suspected role of parity in the ability of cows to cope with starch-rich diets (6).…”
Section: Introductionmentioning
confidence: 99%